Inhibition of Lysenin-induced Hemolysis by All-E-Lutein Derived from the Plant Dalbergia latifolia - Niwa, Yuki; Matsui, Chino; Sukumwang, Neelanun; Iinuma, Hironobu; Ikeda, Yoko; Koyano, Takashi; Kovitayakorn, Taworn; Simizu, Siro; Umezawa, Kazuo (Planta Medica, 2012)
Lysenin is a pore-forming toxin derived from coelomic fluid of the earthworm Eisenia foetida. The model of lysenin-induced hemolysis includes the specific binding of lysenin to sphingomyelin, oligomerization of the pore proteins, and pore formation. Although the mechanism of lysenin-induced hemolysis is unique, its precise mechanism of action and its inhibitors are poorly understood. In the present study, we screened for inhibitors of lysenin-induced hemolysis by using an optimized screening system and found a methanolic extract of Dalbergia latifolia leaves to be a potential candidate. After isolation and identification, all-E-lutein was identified as the hemolysis inhibitor with an effective dose of 0.025–2.5 ng/mL without any toxicity. The inhibition by all-E-lutein is likely to occur during the receptor binding and/or pore-forming protein oligomerization.
Keywords: lysenin; hemolysis; Dalbergia latifolia; Fabaceae; Indian rosewood; Leguminosae; all-E-lutein